MOTIF PESERTA DIDIK BERPERILAKU KONTRADIKTIF TERHADAP LINGKUNGAN DI SMP NEGERI 35 SURABAYA - Safitri, Putri Eka; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2024)
The living environment at school is a very important aspect of education. However, there are still students whose awareness needs to be increased regarding the importance of protecting the environment. The focus and aim of this research is to find out the